Amphibian-derived wound healing peptides: chemical molecular treasure trove for skin wound treatment - Yin, Saige; Wang, Ying; Yang, Xinwang (Frontiers in Pharmacology, 2023)
Amphibian-derived wound healing peptides thus offer new intervention measures and strategies for skin wound tissue regeneration. As novel drug lead molecules, wound-healing peptides can help analyze new mechanisms and discover new drug targets. Previous studies have identified various novel wound-healing peptides and analyzed novel mechanisms in wound healing, especially competing endogenous RNAs (ceRNAs) (e.g., inhibition of miR-663a promotes skin repair). In this paper, we review amphibian-derived wound-healing peptides, including the acquisition, identification, and activity of peptides, a combination of peptides with other materials, and analysis of underlying mechanisms, to better understand the characteristics of wound-healing peptides and to provide a molecular template for the development of new wound repair drugs.